ZAKAT, INFAQ, SADAQAH ON MUSTAHIK INCOME TO REALIZE NO POVERTY IN INDONESIAN ZAKAT INSTITUTION - M Jaenudin; Sri Herianingrum (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2022)
The issue of poverty has become a part of Sustainable Development Goals (SDGs). Islam believes poverty must be sought and given concrete solutions through philanthropic instruments such as zakat, infaq, and sadaqah (ZIS). However, ZIS management will be more optimal if implemented by the Amil Zakat Institution or Lembaga Amil Zakat(LAZ). Thus, this research aims to determine the role of ZIS on mustahik's income for realizing SDGs at the Indonesian zakat institution. The research uses a quantitative method with a comparative approach. The Wilcoxontest will test the data using a different test between mustahik's income before and after being given ZIS funds. In addition, this study also uses several SDGs' indicator metadata, measured through the mustahik's income. Respondents from this research study were mustahik of the ZIS funds provided by Lembaga Manajemen Infaq (LMI), a zakat institution, with a total of 355 respondents spread across the provinces of East Java, South Sumatra, Riau Islands, and South Kalimantan. The results show a difference in the income of LMI mustahik before and after being given ZIS funds. If viewed from the SDGs' indicator metadata perspective, the distribution and utilization of ZISbecome essential in realizing no poverty. The existence of LAZ has an essential role in supporting the SDGs, especially in the equitable distribution of income, and can be an instrument in alleviating poverty. However, suggestions for future research are the need for an approach other than income and also need to be measured using metadata other than the SDGs indicator no poverty.